Temporal Reduction in Chronotropic Index Predicts Risk of Cardiovascular Death Among Healthy Middle‐Aged Men: a 28‐Year Follow‐Up Study - Kristian Engeseth; Christian Hodnesdal; Irene Grundvold; Knut Liestøl; Knut Gjesdal; Sverre E. Kjeldsen; Jan E. Erikssen; Johan Bodegard; Per Torger Skretteberg (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
Background Chronotropic index is a standardized measure of heart rate (HR) increment during exercise that reflects the combined effects of age, resting HR, and physical fitness. Low chronotropic index has been reported to predict disease and death. We tested whether temporal change in chronotropic index over 7 years influenced risk of cardiovascular death through up to 28 years. Methods and Results Chronotropic index was calculated ([achieved maximal HR−resting HR]/[age‐predicted maximal HR−resting HR]) after a symptom‐limited bicycle ECG exercise test in 1420 healthy men at 2 examinations 7 years apart, in 1972 and 1979. Events of cardiovascular death were registered by manual scrutiny of all participants’ hospital charts and the Norwegian Cause of Death Registry. The participants were divided into quartiles of temporal change in chronotropic index, with quartile one having the most negative value. Cox proportional hazard regression models were used to estimate risks and adjusted for classical cardiovascular risk factors. Incidence of cardiovascular death was 310 (22%) during median of 21 years of follow‐up. After multivariable adjustment, and comparison with quartile four (mean +0.11), quartiles one (−0.16), two (−0.04), and three (+0.02) were associated with hazard ratios 1.50 (95% CI 1.10–2.05), 1.10 (0.79–1.53), and 1.04 (0.74–1.45) for cardiovascular death. Results remained robust also after exclusion of 31 participants with exercise ECG‐induced signs of coronary ischemia. Conclusions Temporal reduction in chronotropic index was associated with increased long‐term risk of cardiovascular death and might be a clinically important predictor when assessing risk in healthy individuals over a longer time.